An Overview of Autoimmune and Paraneoplastic Encephalitides - Bradshaw, Michael J.; Linnoila, Jenny J. (Seminars in Neurology, 2018)
The understanding of the manifestations, mechanisms, and management of autoimmune encephalitis has expanded dramatically in recent decades. Immune-mediated encephalitides are comparable in incidence and prevalence to infectious etiologies, and are associated with significant morbidity, especially when there is a delay in recognition and treatment. As such, clinicians from many specialties must develop a functional understanding of these disorders. Herein we provide an overview of the autoimmune and paraneoplastic encephalitides, including those associated with either intracellular or cell surface/synaptic neuronal autoantibodies. After briefly reviewing the current understanding of the pathobiology of autoimmune encephalitis, we combine a neuroanatomical approach with specific antibody syndromes to provide the reader with a clinically relevant review of these disorders. The clinical manifestations, diagnosis, and management of autoimmune encephalitis are reviewed, with an emphasis on clinical relevance. We also introduce updates in the field, including autoimmune encephalitis associated with novel cancer immunotherapies, infectious triggers of autoimmune encephalitis, and autoimmune encephalitis with demyelinating overlap syndromes.
Keywords: autoimmune; paraneoplastic; encephalitis; antibodies; immunotherapy